Procedure for exercising the rights of a person unfoundedly deprived of liberty of unfounded convicted - Milovanović, Dragana (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2021)
The Code of Criminal Procedure provides a special procedure for exercising the rights of a person unjustifiably deprived of liberty or unjustifiably convicted. The introduction of such a procedure in the criminal legislation of the Republic of Serbia occurs as a consequence of an enormous number of acquittals, after the most difficult measure of     ensuring the presence of the accused in the criminal procedure was carried out against the defendant during the procedure. Also, this procedure appeared necessary for the purpose of compensating the convict in those situations, when after the submission of extraordinary   legal remedies, the final court decision was changed, and the unfounded convict was released. In such situations, a procedure covers two phases - the first phase is an administrative procedure, while the second phase is a court procedure. The phases are connected, so that the court procedure is initiated only if the administrative procedure is not resolved in favor of the injured party. Proceedings are initiated by the injured party, who primarily submits a request for the purposeful realization of his legal rights. If he does not exercise his rights in this way, the injured party has the right to initiate proceedings before the competent court against the Republic of Serbia as a responsible party.
Keywords: wrongfully convicted; wrongfully detained; damage compensation claim; procedure; fair compensation